2017
DOI: 10.1007/s12029-017-9928-7
|View full text |Cite
|
Sign up to set email alerts
|

DNMT3B −579 G>T Promoter Polymorphism and the Risk of Gastric Cancer in the West of Iran

Abstract: Our study suggested that the -579 T allele may increase the relative risk for the progression of clinicopathological characteristic of tumor grade of gastric cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…This result is almost in agreement with the findings of a previous study which investigated the association of DNMT3B-579G>T polymorphism with gastric cancer in Iranian population (a frequency of 60.71% and 39.29% for G allele and minor allele, T, respectively, among controls). 21 These results also were relatively consistent with those revealed in European population (a frequency of 65.0% and 35.0% for G and T alleles, respectively, among controls). 20,27 However, the results of the present study were different from those observed in other Asian populations with a higher frequency of T allele than G allele for DNMT3B-579G>T polymorphism.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result is almost in agreement with the findings of a previous study which investigated the association of DNMT3B-579G>T polymorphism with gastric cancer in Iranian population (a frequency of 60.71% and 39.29% for G allele and minor allele, T, respectively, among controls). 21 These results also were relatively consistent with those revealed in European population (a frequency of 65.0% and 35.0% for G and T alleles, respectively, among controls). 20,27 However, the results of the present study were different from those observed in other Asian populations with a higher frequency of T allele than G allele for DNMT3B-579G>T polymorphism.…”
Section: Discussionsupporting
confidence: 90%
“…The results of a study conducted in a subset of Iranian patients with gastric cancer suggested that the DNMT3B-579T allele might increase the relative risk for the progression of clinicopathological characteristic of tumor grade in affected individuals. 21 Also, this allele showed a significant difference between patients with gastric cancer and control group in population of China. 22 There was no significant relationship between DNMT3B-579G>T and gallbladder carcinoma in Indian population.…”
Section: Discussionmentioning
confidence: 91%
“…However, there is conflicting evidence on the contribution of these two SNPs in different cancers [140][141][142][143]. Hu et al [144] and Chen et al [145] reported the association of rs1569686 with gastric cancer risk in the Chinese population, while Wang et al [146] and Ahmadi et al [147] did not observe any significant association in the Chinese and Iranian population, respectively. Likewise, other studies demonstrated that rs2424913 was irrelevant to the risk of gastric carcinogenesis [144][145][148][149][150].…”
Section: Polymorphisms In Dnmts and Gastric Cancer Developmentmentioning
confidence: 99%
“…In this regard, serious life-threatening health difficulties are more likely among individuals with diabetes, which would significantly affect the therapeutic care cost, lower the quality of life and enhance mortality (5)(6)(7)(8). Evidence implies that the production of reactive oxygen species (oxidative stress) can exacerbate hyperglycemia and increase the risk of diabetes complications (microvascular or cardiovascular) (9).…”
Section: Introductionmentioning
confidence: 99%